1985
DOI: 10.1111/j.1755-3768.1985.tb01589.x
|View full text |Cite
|
Sign up to set email alerts
|

Pigmentary dispersion syndrome A biometric study

Abstract: A-Scan biometry was performed on both eyes of 5 patients suffering from unilateral pigmentary dispersion syndrome, partly with glaucoma. The anterior chamber was significantly deeper and the lens significantly flatter in the eyes with pigmentary dispersion syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Male PDS patients have been shown to have deeper ACs than female PDS patients 30 . The deeper ACs of men, myopes and young people reported in biometric studies correlate well with the clinical characteristics of PDS and PG 14,29 …”
Section: Pigment Dispersion Syndromementioning
confidence: 74%
See 1 more Smart Citation
“…Male PDS patients have been shown to have deeper ACs than female PDS patients 30 . The deeper ACs of men, myopes and young people reported in biometric studies correlate well with the clinical characteristics of PDS and PG 14,29 …”
Section: Pigment Dispersion Syndromementioning
confidence: 74%
“…Caprioli reported that the ACs of patients with PDS were deeper than those with primary open angle glaucoma (POAG) when corrected for age and refraction 26 . The ACs of eyes with PDS appear deepest at 3.5 mm below axis 27 , and in asymmetric cases the ACs were deeper in the most affected eye, suggesting that deep ACs have a role in the pathogenesis 28,29 . Male PDS patients have been shown to have deeper ACs than female PDS patients 30 .…”
Section: Pigment Dispersion Syndromementioning
confidence: 99%
“…In PDS and pigmentary glaucoma, it has been hypothesized that pigment is sloughed from the posterior iris surface by lens zonules that rub against the iridial tissue. 1,37,38 Structural abnormalities of the middle third of the eye have been noted in PDS. The size of the iris appears to be overly large relative to that of the anterior segment.…”
Section: Resultsmentioning
confidence: 99%